Protection of economic rights of authors of traditional songs in Tanzania: Assessment of the law and practice - Sivonike, B. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the Degree of Master of Laws in Commercial (LL.M-CL) of Mzumbe University